Method for regenerating alkali lignin into sodium ion battery negative electrode material and sodium ion battery negative electrode material
By absorbing cadmium ions and zinc ions and high -temperature vulcanization of alkaline carbon -based carbon, the alkaline wood quality biological carbon load CD and Zn's sulfide negative materials are prepared, which solves the high cost of preparation of negative electrode materials for sodium ion batteries and complex craftsmanship The problem has achieved low -cost, low -energy negative materials preparation, and has good electrochemical properties.
Patent Information
- Application Number
- CN202411544082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing sodium ion battery negative electrode materials are cost-effective and complex in preparation, so they are not suitable for large-scale applications.
After heat treatment of alkali wood, cadmium ions and zinc ions are adsorbed, and the alkaline wood quality biological carbon load CD and Zn's sulfide negative materials are prepared by high temperature vulcanization.
The negative material of low -cost, low -energy -consuming regenerative sodium ion battery has good electrochemical properties and suitable for large -scale applications.
Smart Images

Figure CN119361649A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to the recycling of alkali lignin. Background Art
[0002] Since the 21st century, the rapid consumption of fossil fuels has led to the rapid development of global warming, and the development of green and friendly renewable energy is imminent. With the development of industry, the amount of industrial solid waste generated is very large, and its utilization rate is only 57%. Using waste as a cheap raw material to achieve the effect of reducing costs and improving performance may be an important measure to solve this problem. Therefore, the use of waste biomass as energy storage electrode materials has great potential.
[0003] In recent years, many different waste biomasses have been used in lithium battery research, such as coffee grounds, wheat flour, sisal fiber, etc., and good results have been achieved. According to the 2022 World Energy Statistical Review, the price of lithium carbonate has risen by 58%, averaging $11,000 per ton. The high price of lithium is inconsistent with our original intention of studying waste biomass, and sodium batteries have attracted attention as an alternative to lithium batteries. Unlike lithium, there are abundant sodium reserves on the earth, so the cost is low. Although sodium ions themselves are abundant and relatively cheap, the preparation cost of some high-performance negative electrode materials (such as hard carbon, transition metal oxides, etc.) is high, which directly affects the overall cost of the battery.
[0004] The prior art discloses some methods of using titanium-based composite materials, metal organic frameworks, etc. as negative electrode materials for sodium ion batteries. However, they are expensive, the preparation process is complicated, and they are not suitable for large-scale application. Hard carbon is the most widely used negative electrode material for sodium ion batteries. Although the raw material cost of hard carbon is not high, its preparation process is complicated and the energy consumption is high, which increases the cost of the final product. Summary of the invention
[0005] In response to the above technical problems, the present application provides a method for regenerating alkaline lignin into a negative electrode material for a sodium ion battery and a negative electrode material for a sodium ion battery.
[0006] To achieve the above objectives, this application proposes the following solutions: In a first aspect, a method for regenerating alkali lignin into a negative electrode material for a sodium ion battery is provided, comprising: The alkali lignin is heat treated to obtain alkali lignin biochar; the alkali lignin biochar is added with Cd 2+ and Zn 2+ In the aqueous solution containing metal ions, alkaline lignin biochar was used to adsorb Cd in the aqueous solution containing metal ions. 2+ and Zn 2+ions to obtain alkali lignin biochar adsorbed with heavy metals; placing the alkali lignin biochar adsorbed with heavy metals and a sulfur source in a furnace body, introducing an inert gas into the furnace body to maintain an inert atmosphere in the furnace body, and sintering to obtain alkali lignin biochar loaded with Cd and Zn sulfides, wherein the gas flow direction of the inert gas is from the sulfur source to the alkali lignin biochar.
[0007] Preferably, the Cd in the metal ion-containing aqueous solution 2+ and Zn 2+ The molar concentration ratio is 2.8~3.3:1.
[0008] Preferably, the Cd in the metal ion-containing aqueous solution 2+ The ion concentration is 150~1200ppm.
[0009] Preferably, the adsorption time is 1 to 2 hours; and the adsorption is performed with the assistance of mechanical force.
[0010] Preferably, after the adsorption treatment, the method further includes drying the alkali lignin biochar adsorbed with heavy metals.
[0011] Preferably, the alkaline lignin biochar is used to adsorb Cd in the aqueous solution containing metal ions. 2+ and Zn 2+ ions, the dosage of the alkali lignin biochar is 0.1-0.3 g of alkali lignin biochar per 100 mL of the aqueous solution containing metal ions.
[0012] Preferably, the sulfur source is thiourea; and the mass ratio of the sulfur source to the alkali lignin biochar is 2:1 to 5:1.
[0013] Preferably, the sintering temperature is 500-700° C. and the sintering time is 1-4 hours.
[0014] Preferably, the method for preparing the alkali lignin biochar comprises: subjecting the alkali lignin to microwave sintering and carbonization in an inert gas atmosphere to obtain the alkali lignin biochar.
[0015] Preferably, the carbonization is followed by grinding; preferably, the particle size of the alkali lignin biochar obtained after grinding is less than 100 mesh.
[0016] Preferably, the obtained alkali lignin biochar is stored under a vacuum environment.
[0017] Preferably, the microwave sintering temperature is 400-500° C.; the microwave sintering time is 15-60 minutes.
[0018] Preferably, the method further comprises subjecting the alkali lignin biochar obtained by sintering to Cd and Zn sulfides loaded thereon with PDA (polydopamine) coating modification.
[0019] Preferably, the sulfide of Cd and Zn is Cd 7.23 Zn 2.77 S 10 .
[0020] In a second aspect, a negative electrode material for a sodium ion battery is provided, which is prepared using the aforementioned method.
[0021] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The sulfides of Cd and Zn loaded on the alkali lignin biochar, a negative electrode material for sodium ion batteries, regenerated by the method of the present invention, have good electrochemical properties and good application prospects.
[0022] The method of the present invention can use agricultural waste such as alkali lignin as a carbon base and regenerate it into a negative electrode material for sodium ion batteries. The treatment method requires abundant raw materials, low sintering temperature, and low energy consumption, so the cost of regeneration is low and can be widely used. In addition, the treatment method can realize the resource utilization of alkali lignin, which accounts for a large proportion of agricultural waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 1 is the XRD diagram of the composite negative electrode material prepared in Examples 1, 2 and 3.
[0025] Figure 2 The following are SEM images of the composite negative electrode material prepared in Example 1 at different magnifications.
[0026] Figure 3 (a) charge-discharge curves of the first three cycles and (b) cycle performance curve of the button cell assembled with the composite negative electrode material prepared in Example 1 at 100 mA / g.
[0027] Figure 4 (a) charge-discharge curves of the first three cycles and (b) cycle performance curve of the button cell assembled with the composite negative electrode material prepared in Example 1 at 500 mA / g.
[0028] Figure 5The following are SEM images of the composite negative electrode material prepared in Example 2 at different magnifications.
[0029] Figure 6 This is the surface distribution component analysis of the composite negative electrode material prepared in Example 2.
[0030] Figure 7 (a) charge-discharge curves of the first three cycles and (b) cycle performance curve of the button cell assembled with the composite negative electrode material prepared in Example 2 at 100 mA / g.
[0031] Figure 8 (a) charge-discharge curves of the first three cycles and (b) cycle performance curve of the button cell assembled with the composite negative electrode material prepared in Example 2 at 500 mA / g.
[0032] Fig. 9 The following are SEM images of the composite negative electrode material prepared in Example 3 at different magnifications.
[0033] Fig.10 (a) charge-discharge curves of the first three cycles and (b) cycle performance curve of the button cell assembled with the composite negative electrode material prepared in Example 3 at 100 mA / g.
[0034] Fig.11 (a) charge-discharge curves of the first three cycles and (b) cycle performance curve of the button cell assembled with the composite negative electrode material prepared in Example 3 at 500 mA / g.
[0035] Fig.12 The cycle performance curve of the button-type battery assembled with the negative electrode material prepared in Comparative Example 1 at 500 mA / g.
[0036] Fig.13 The cycle performance curve of the button-type battery assembled with the negative electrode material prepared in Comparative Example 2 at 100 mA / g.
[0037] Fig.14 The cycle performance curve of the button-type battery assembled with the negative electrode material prepared in Comparative Example 3 at 100 mA / g.
[0038] Fig.15 The cycle performance curve of the button cell assembled with the coated modified composite negative electrode material prepared in Example 4 at 100 mA / g. DETAILED DESCRIPTION
[0039] In view of the high cost of using hard carbon as negative electrode material in the prior art, the applicant tried to use common waste alkali lignin to regenerate biochar as negative electrode material. However, the applicant found in the research process that the alkali lignin biochar obtained by conventional heat treatment has extremely low capacity when used as negative electrode material. In view of this phenomenon, the applicant found through research that the alkali lignin biochar obtained by adsorbing cadmium ions and zinc ions and then subjecting it to high temperature sulfidation can prepare alkali lignin biochar loaded with Cd and Zn sulfide negative electrode materials, especially alkali lignin biochar loaded with Cd 7.23 Zn 2.77 S 10 The electrical properties of the negative electrode material are greatly improved. Based on this, the present invention is completed.
[0040] A method for regenerating alkali lignin into a negative electrode material for a sodium ion battery, comprising: The alkali lignin is heat treated to obtain alkali lignin biochar; the alkali lignin biochar is added with Cd 2+ and Zn 2+ In the aqueous solution containing metal ions, alkaline lignin biochar was used to adsorb Cd in the aqueous solution containing metal ions. 2+ and Zn 2+ ions to obtain alkali lignin biochar adsorbed with heavy metals; placing the alkali lignin biochar adsorbed with heavy metals and a sulfur source in a furnace body, introducing an inert gas into the furnace body to maintain an inert atmosphere in the furnace body, and sintering to obtain a sulfide negative electrode material of the alkali lignin biochar loaded with Cd and Zn, wherein the gas flow direction of the inert gas is from the sulfur source to the alkali lignin biochar.
[0041] In some preferred embodiments, the Cd 2+ and Zn 2+ The molar concentration ratio is 2.8~3.3:1.
[0042] In some preferred embodiments, the Cd 2+ The ion concentration is 150~1200ppm.
[0043] In some preferred embodiments, the adsorption time is 1 to 4 hours; the adsorption is performed with the assistance of a mechanical force, and the mechanical force can be achieved, for example, by shaking, ultrasound, or stirring.
[0044] In some preferred embodiments, the step of drying the alkali lignin biochar adsorbed with heavy metals is further included after the adsorption treatment.
[0045] In some preferred embodiments, the alkali lignin biochar is used to adsorb Cd in the aqueous solution containing metal ions. 2+ and Zn2+ ions, the dosage of the alkali lignin biochar is 0.1-0.3 g of alkali lignin biochar per 100 mL of the aqueous solution containing metal ions.
[0046] In some preferred embodiments, the sulfur source is thiourea; and the mass ratio of the sulfur source to the alkali lignin biochar is 2:1 to 4:1.
[0047] In some preferred embodiments, the sintering temperature is 500-700° C.; and the sintering time is 1-4 hours.
[0048] In some preferred embodiments, the method for preparing the alkali lignin biochar comprises: subjecting the alkali lignin to microwave sintering and carbonization in an inert gas atmosphere to obtain the alkali lignin biochar.
[0049] Preferably, the carbonization is followed by grinding; preferably, the particle size of the alkali lignin biochar obtained after grinding is less than 100 mesh.
[0050] The obtained alkali lignin biochar is preferably stored under a vacuum environment.
[0051] In some preferred embodiments, the microwave sintering temperature is 400-500° C.; and the microwave sintering time is 15-60 minutes.
[0052] In some preferred embodiments, the inert gas is one or both of nitrogen and argon.
[0053] The sintering can be carried out in a tubular furnace, and the time for passing argon through the tubular furnace should be determined according to the size of the tubular furnace and the rate of passing argon, and should be at least more than 30 minutes. The tubular furnace can also be replaced by a furnace that can provide a high vacuum environment or an environment filled with argon and a high temperature.
[0054] In some preferred embodiments, the alkali lignin biochar loaded with Cd and Zn sulfides obtained by sintering is further modified by PDA coating. The PDA coating modification can adopt an existing conventional coating method, such as preparing a tris(hydroxymethyl)aminomethane hydrochloride buffer solution, then adding dopamine hydrochloride, mixing evenly to obtain a dopamine hydrochloride solution, then adding the negative electrode material to the dopamine hydrochloride solution, stirring and reacting, washing, and drying to obtain a PDA-coated modified composite negative electrode material.
[0055] The present invention also provides a sodium ion battery negative electrode material, which is prepared by the above method. Preferably, the sodium ion battery negative electrode material is alkaline lignin biochar and Cd 7.23 Zn 2.77 S 10 Composite material of negative electrode material, and the Cd 7.23 Zn 2.77 S 10The negative electrode material is loaded on the alkali lignin biochar.
[0056] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0057] Example 1 The alkali lignin was placed in a porcelain boat and heated at 400°C for 15 minutes in an argon atmosphere in a microwave tube furnace to obtain alkali lignin biochar. The alkali lignin was ground with an agate mortar to obtain finer particles, which were then sieved and stored in vacuum-sealed bags.
[0058] Prepare 1L Cd 2+ The ion concentration is 150ppm, Zn 2+ The metal solution has an ion concentration of 50 ppm. Weigh 0.4 g of alkali lignin biochar, put it into 200 mL of the metal solution, shake it for 1 h, filter it, and dry it in an oven at 60°C to obtain material 1.
[0059] The porcelain boat containing material 1 was placed in a tube furnace, and a porcelain boat containing 0.8 g of thiourea was placed next to it (at the ventilation end), and high-purity argon was passed through to remove the air in the furnace. Then, the material was sulfurized at 700°C for 2 h in an argon atmosphere to obtain the negative electrode material. The XRD pattern of the obtained negative electrode material is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the obtained negative electrode material has Cd 7.23 Zn 2.77 S 10 The characteristic peaks of the materials are not visible. The characteristic peaks of ZnS and CdS are not visible. At the same time, combined with the raw materials, it can be determined that the final prepared negative electrode material is carbon and Cd 7.23 Zn 2.77 S 10 Composite materials of materials. The SEM images of the obtained negative electrode materials at different magnifications (5000 times and 20000 times) are as follows Figure 2 As shown, from Figure 2 It can be seen that when the metal ion concentration in the metal solution is low, the obtained composite negative electrode material is granular.
[0060] The obtained negative electrode materials were assembled into sodium ion button half-cells for charge and discharge tests.
[0061] Transfer the prepared electrode sheet into an inert atmosphere glove box and prepare the button cell assembly components: negative electrode shell, sodium metal sheet, diaphragm, gasket, spring sheet, positive electrode shell, electrolyte, as well as tablet pressing mold, pipette and insulated tweezers.
[0062] Assembly process: Place the negative electrode shell flat on an insulating table, place the metal sodium sheet in the center of the negative electrode shell, and use a tablet pressing mold to flatten the metal sodium sheet, then place the diaphragm flat on the upper layer of the sodium sheet, and use a pipette to take an appropriate amount of electrolyte and drop it on the surface of the diaphragm. Use insulating tweezers to place the test electrode, gasket, spring sheet and positive electrode shell on the upper layer of the diaphragm in sequence. Use insulating tweezers to place the button battery with the negative side facing up on the button battery sealing machine mold. You can use a paper towel to pad the top of the battery to absorb the overflowed electrolyte. Adjust the pressure and press for 30 seconds to complete the assembly of the button battery. Take it out with insulating tweezers, observe whether the appearance of the preparation is complete and wipe it clean with a paper towel.
[0063] The button cell assembled with the negative electrode material prepared in this example has (a) the charge-discharge curves of the first three cycles and (b) the cycle performance curves at 100 mA / g. Figure 3 As shown, the charge-discharge curves of (a) the first three cycles and (b) the cycle performance curves at 500 mA / g are shown in Figure 4 shown.
[0064] from Figure 3 and Figure 4 It can be seen that when discharging at a constant current of 100mA, the first discharge capacity was measured to be 658mAh / g, and after 100 cycles, the discharge capacity was 178mAh / g; when discharging at a constant current of 500mA, the first discharge capacity was measured to be 615mAh / g, and after 100 cycles, the discharge capacity was 156mAh / g.
[0065] Example 2 The alkali lignin was placed in a porcelain boat and heated at 400°C for 15 minutes in an argon atmosphere in a microwave tube furnace to obtain alkali lignin biochar. The alkali lignin was ground with an agate mortar to obtain finer particles, which were then sieved and stored in vacuum-sealed bags.
[0066] Prepare 1L Cd 2+ The ion concentration is 300ppm, Zn 2+ Metal solution with an ion concentration of 100 ppm. Weigh 0.4 g of alkali lignin biochar, put it into 200 mL of metal solution, shake for 1 h, filter, and dry in an oven at 60 ° C to obtain material 1.
[0067] The porcelain boat containing material 1 was placed in a tube furnace, and a porcelain boat containing 0.8 g of thiourea was placed next to it (at the ventilation end), and high-purity argon was passed through to remove the air in the furnace. Then, the material was sulfurized at 700°C for 2 h in an argon atmosphere to obtain the negative electrode material. The XRD pattern of the obtained negative electrode material is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the obtained negative electrode material has Cd 7.23 Zn 2.77 S 10The characteristic peaks of the materials are not visible. The characteristic peaks of ZnS and CdS are not visible. At the same time, combined with the raw materials, it can be determined that the final prepared negative electrode material is carbon and Cd 7.23 Zn 2.77 S 10 Composite materials of materials. The SEM images of the obtained negative electrode materials at different magnifications (5000 times and 20000 times) are as follows Figure 5 As shown, from Figure 5 It can be seen that as the concentration of metal ions in the metal solution increases, rod-shaped crystals appear in the obtained composite negative electrode material. The surface distribution component analysis diagram of the obtained negative electrode material is shown in Figure 2. Figure 6 As shown, from Figure 6 It can be seen that the Cd, Zn and S elements are evenly distributed in the prepared negative electrode material.
[0068] The obtained negative electrode materials were assembled into sodium ion button half-cells for charge and discharge tests.
[0069] The button cell assembled with the negative electrode material prepared in this example has (a) the charge-discharge curves of the first three cycles and (b) the cycle performance curves at 100 mA / g. Figure 7 As shown, the charge-discharge curves of (a) the first three cycles and (b) the cycle performance curves at 500 mA / g are shown in Figure 8 shown.
[0070] from Figure 7 and Figure 8 It can be seen that when the assembled button battery is discharged at a constant current of 100mA, the initial discharge capacity is 735mAh / g, the discharge capacity after 50 cycles is about 270mAh / g, and the discharge capacity after 100 cycles is 211mAh / g; when discharged at a constant current of 500mA, the initial discharge capacity is 676mAh / g, and after 100 cycles, the discharge capacity is 185mAh / g.
[0071] Example 3 The alkali lignin was placed in a porcelain boat and heated at 400°C for 15 minutes in an argon atmosphere in a microwave tube furnace to obtain alkali lignin biochar. The alkali lignin was ground with an agate mortar to obtain finer particles, which were then sieved and stored in vacuum-sealed bags.
[0072] Prepare 1L Cd 2+ The ion concentration is 600ppm, Zn 2+ Metal solution with an ion concentration of 200 ppm. Weigh 0.4 g of alkali lignin biochar, put it into 200 mL of metal solution, shake for 1 h, filter, and dry in an oven at 60 ° C to obtain material 1.
[0073] The porcelain boat containing material 1 was placed in a tube furnace, and a porcelain boat containing 0.8 g of thiourea was placed next to it (at the ventilation end), and high-purity argon was passed through to remove the air in the furnace. Then, the material was sulfurized at 700°C for 2 h in an argon atmosphere to obtain the negative electrode material. The XRD pattern of the obtained negative electrode material is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the obtained negative electrode material has Cd 7.23 Zn 2.77 S 10 The characteristic peaks of the materials are not visible. The characteristic peaks of ZnS and CdS are not visible. At the same time, combined with the raw materials, it can be determined that the final prepared negative electrode material is carbon and Cd 7.23 Zn 2.77 S 10 The XRD patterns of the negative electrode materials obtained by comparing Examples 1 to 3 show that changing the concentration does not affect the formation of the crystalline phase.
[0074] The SEM images of the obtained negative electrode material at different magnifications (5000 times and 20000 times) are as follows: Fig. 9 As shown, from Fig. 9 It can be seen that as the metal ion concentration in the metal solution further increases, the material clusters into spheres. Comparing the morphology of the negative electrode materials prepared in Examples 1 to 3, it is found that as the metal ion concentration changes, the morphology of the negative electrode material also changes. After analysis, the rod-like and spherical morphology materials correspond to the sulfide in the composite material.
[0075] The obtained negative electrode materials were assembled into sodium ion button half-cells for charge and discharge tests.
[0076] The button cell assembled with the negative electrode material prepared in this example has (a) the charge-discharge curves of the first three cycles and (b) the cycle performance curves at 100 mA / g. Fig.10 As shown, the charge-discharge curves of (a) the first three cycles and (b) the cycle performance curves at 500 mA / g are shown in Fig.11 shown.
[0077] from Fig.10 and Fig.11 It can be seen that when the button battery assembled with the negative electrode material prepared in this embodiment is discharged at a constant current of 100mA, the measured first discharge specific capacity is 680mAh / g, and after 100 cycles, the discharge specific capacity is 144mAh / g; the button battery assembled with the negative electrode material prepared in this embodiment is discharged at a constant current of 500mA, and the measured first discharge specific capacity is 630mAh / g. After 100 cycles, the measured discharge specific capacity is 125mAh / g.
[0078] Comparative Example 1 The alkali lignin was placed in a porcelain boat and heated at 400°C for 15 minutes in an argon atmosphere in a microwave tube furnace to obtain alkali lignin biochar. The alkali lignin was ground with an agate mortar to obtain finer particles, which were then sieved and stored in vacuum-sealed bags.
[0079] Weigh 0.4 g of alkali lignin biochar into a porcelain boat, put the porcelain boat into a tubular furnace, pass high-purity argon gas, remove the air in the boat, and then treat it at 700°C for 2 h in an argon atmosphere to obtain a negative electrode material.
[0080] The obtained negative electrode materials were assembled into sodium ion button half-cells for charge and discharge tests.
[0081] The cycle performance curve of the sodium ion button half-cell assembled with the negative electrode material prepared in Comparative Example 1 at 500 mA / g is as follows: Fig.12 As shown, by comparing the cycle performance curves of each embodiment and comparative example 1, it can be seen that the electrical properties of the composite modified alkali lignin biochar of each embodiment are greatly improved.
[0082] Comparative Example 2 The alkali lignin was placed in a porcelain boat and heated at 400°C for 15 minutes in an argon atmosphere in a microwave tube furnace to obtain alkali lignin biochar. The alkali lignin was ground with an agate mortar to obtain finer particles, which were then sieved and stored in vacuum-sealed bags.
[0083] Prepare 1L Cd 2+ The metal solution has an ion concentration of 400 ppm. Weigh 0.4 g of alkali lignin biochar, put it into 200 mL of metal solution, shake for 1 h, filter, and dry in an oven at 60° C. to obtain material 1.
[0084] Put the porcelain boat containing material 1 into a tubular furnace, and place a porcelain boat containing 0.8g of thiourea next to it (at the venting end). Pass high-purity argon gas through it to remove the air in the air, and then perform a sulfurization treatment at 700℃ for 2h in an argon atmosphere to obtain the negative electrode material.
[0085] The obtained negative electrode materials were assembled into sodium ion button half-cells for charge and discharge tests.
[0086] The cycle performance curve of the sodium ion button half-cell assembled with the negative electrode material prepared in Comparative Example 2 at 100 mA / g is as follows: Fig.13 As shown, from Fig.13 It can be seen that its first discharge specific capacity is about 688 mAh / g, and the discharge specific capacity after 50 cycles is about 259 mAh / g.
[0087] By comparing the button cells assembled in Example 2 and Comparative Example 2, it can be seen that the electrical properties of the composite modified alkali lignin biochar prepared in Example 2 are significantly improved compared with the single CdS-modified alkali lignin biochar.
[0088] Comparative Example 3 The alkali lignin was placed in a porcelain boat and heated at 400°C for 15 minutes in an argon atmosphere in a microwave tube furnace to obtain alkali lignin biochar. The alkali lignin was ground with an agate mortar to obtain finer particles, which were then sieved and stored in vacuum-sealed bags.
[0089] Prepare 1L Zn 2+ The metal solution has an ion concentration of 400 ppm. Weigh 0.4 g of alkali lignin biochar, put it into 200 mL of metal solution, shake for 1 h, filter, and dry in an oven at 60° C. to obtain material 1.
[0090] Put the porcelain boat containing material 1 into a tubular furnace, and place a porcelain boat containing 0.8g of thiourea next to it (at the venting end). Pass high-purity argon gas through it to remove the air in the air, and then perform a sulfurization treatment at 700℃ for 2h in an argon atmosphere to obtain the negative electrode material.
[0091] The obtained negative electrode materials were assembled into sodium ion button half-cells for charge and discharge tests.
[0092] The cycle performance curve of the sodium ion button half-cell assembled with the negative electrode material prepared in Comparative Example 3 at 100 mA / g is as follows: Fig.14 As shown, from Fig.14 It can be seen that its first discharge specific capacity is about 729 mAh / g, and the discharge specific capacity after 50 cycles is about 190 mAh / g.
[0093] By comparing the button cells assembled in Example 2 and Comparative Example 3, it can be seen that the electrical properties of the composite modified alkali lignin biochar prepared in Example 2 are significantly improved compared with the single ZnS modified alkali lignin biochar.
[0094] By comprehensively comparing the electrical properties of button cells assembled with modified alkali lignin biochars of Example 2, Comparative Example 2 and Comparative Example 3, it can be found that the electrical performance of the composite modified alkali lignin biochar is better than that of the CdS modified alkali lignin biochar of Comparative Example 2, and the modification effect is more significant than that of the single ZnS modified alkali lignin biochar of Comparative Example 3.
[0095] Example 4 The difference between this embodiment and embodiment 2 is that it also includes the step of further PDA coating modification of the prepared composite modified alkali lignin biochar negative electrode material, specifically including: First, prepare 100mL of 10mmol / L tris(hydroxymethyl)aminomethane hydrochloride buffer solution, adjust the pH to 8.5 with 0.1mol / L hydrochloric acid; then add 0.2g dopamine hydrochloride, and ultrasonicate for 5 minutes; weigh 1g of the composite material prepared in Example 2 and add it to the dopamine hydrochloride solution, stir at room temperature for 24h. Then wash with ultrapure water, put in a 60℃ oven to dry for 12h, and store in bags.
[0096] The cycle performance curve of the button cell assembled with the obtained coated modified composite negative electrode material at a current density of 100 mA / g is as follows: Fig.15 As shown, from Fig.15 It can be concluded that the battery has an initial discharge capacity of 753 mAh / g, and a discharge capacity of about 286 mAh / g after 50 cycles. Comparing the data of Example 2 with that of Example 4, it can be seen that the battery's cycle performance can be further improved by further PDA coating modification. After analysis, this may be because PDA coating inhibits the expansion of the negative electrode material and improves its structural stability.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for regenerating alkali lignin into a negative electrode material for a sodium ion battery, characterized in that: include: The alkali lignin is heat treated to obtain alkali lignin biochar; the alkali lignin biochar is added with Cd 2+ and Zn 2+ In the aqueous solution containing metal ions, alkaline lignin biochar was used to adsorb Cd in the aqueous solution containing metal ions. 2+ and Zn 2+ , obtaining alkali lignin biochar adsorbing heavy metals; Alkali lignin biochar adsorbed with heavy metals and a sulfur source are placed in a furnace body, and an inert gas is introduced into the furnace body to maintain an inert atmosphere in the furnace body for sintering to obtain alkali lignin biochar loaded with Cd and Zn sulfides as a negative electrode material for sodium ion batteries, wherein the gas flow direction of the inert gas is from the sulfur source to the alkali lignin biochar.
2. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The Cd in the aqueous solution containing metal ions 2+ and Zn 2+ The molar concentration ratio is 2.8~3.3:1; The Cd in the aqueous solution containing metal ions 2+ The ion concentration is 150~1200ppm.
3. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The adsorption time is 1 to 2 hours; the adsorption is performed with the assistance of mechanical force; Preferably, after the adsorption treatment, the method further includes a step of drying the alkali lignin biochar adsorbed with heavy metals.
4. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The method uses alkali lignin biochar to adsorb Cd in a metal ion-containing aqueous solution 2+ and Zn 2+ ions, the dosage of the alkali lignin biochar is 0.1-0.3 g of alkali lignin biochar per 100 mL of the aqueous solution containing metal ions.
5. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The sulfur source is thiourea; the mass ratio of the sulfur source to the alkali lignin biochar is 2:1 to 5:
1.
6. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The sintering temperature is 500-700° C. and the sintering time is 1-4 hours.
7. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The preparation method of the alkali lignin biochar comprises: subjecting the alkali lignin to microwave sintering and carbonization in an inert gas atmosphere to obtain the alkali lignin biochar; Preferably, grinding is performed after carbonization; preferably, the particle size of the alkali lignin biochar obtained after grinding is less than 100 mesh; Preferably, the obtained alkali lignin biochar is stored under a vacuum environment; Preferably, the microwave sintering temperature is 400-500° C.; the microwave sintering time is 15-60 minutes.
8. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: It also includes PDA coating modification of the alkali lignin biochar loaded with Cd and Zn sulfides obtained by sintering.
9. The method for regenerating alkali lignin into a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The sulfide of Cd and Zn is Cd 7.23 Zn 2.77 S 10 .
10. A negative electrode material for a sodium ion battery, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation and application of biomass carbon / sulfur composite material
CN110176597A
Lignin-based carbon-supported zinc sulfide as well as preparation method and application thereof
CN117285026A
Hard carbon negative electrode material and preparation method therefor, mixed negative electrode material, and secondary battery
WO2024108771A1
Cited By
In-situ deposition coated phosphorus-carbon negative electrode material as well as preparation method and application thereof
CN120149385A
In-situ Deposited Coated Phosphorus-Carbon Anode Material and Its Preparation Method and Application
CN120149385B
Preparation of lignin-based monatomic hard carbon material, hard carbon material and secondary battery
CN121757845A